Multilevel Intergroup Contact and Antigay Prejudice (Explicit and Implicit): Evidence of Contextual Contact Benefits in a Less Visible Group Domain. (April 2017) - MacInnis, Cara C.; Page-Gould, Elizabeth; Hodson, Gordon
Intergroup contact at the individual level is robustly associated with lower prejudice, but intergroup contact occurs within a greater regional context. Multilevel examinations thus far have focused on interethnic contact, where both individual- and contextual-level contact are associated with lower explicit prejudice. Given that ethnicity is visible, two lingering questions concern whether (a) contextual contact effects only apply to visible outgroups and (b) contextual contact effects predict implicit prejudice in addition to explicit prejudice. In two studies, we tested these questions in the domain of sexual orientation. Individual- and contextual-level contact were simultaneously (uniquely) associated with lower implicit and explicit prejudice: Individuals having more contact with gay men/lesbians were less prejudiced toward gay men and lesbians, and individuals living in areas with greater contact with gay men/lesbians were less prejudiced toward gay men/lesbians. It seems that people need not directly witness intergroup contact in their region for contextual contact effects to occur.